2013
DOI: 10.1161/hypertensionaha.111.00645
|View full text |Cite
|
Sign up to set email alerts
|

Renal Denervation Abolishes the Age-Dependent Increase in Blood Pressure in Female Intrauterine Growth-Restricted Rats at 12 Months of Age

Abstract: Perinatal insults program sex differences in blood pressure, with males more susceptible than females. Aging may augment developmental programming of chronic disease, but the mechanisms involved are not clear. We previously reported that female growth-restricted offspring are normotensive after puberty. Therefore, we tested the hypothesis that age increases susceptibility to hypertension in female growth-restricted offspring. Blood pressure remained similar at 6 months of age; however, blood pressure was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 38 publications
(61 reference statements)
9
100
0
1
Order By: Relevance
“…In the IUGR LPD females, it is possible that the initial congenital deficit combined with aging has markedly depleted renal functional reserve and, thus, counteracted the beneficial hormonal effects of circulating estrogen. In support of this idea, a congenital deficit in nephron number has been linked to an age-related decline in renal function in females in other animal programming models [including placental insufficiency (24,38), fetal uninephrectomy (54), and maternal nicotine (55)]. It has been suggested that kidneys with fewer nephrons are more sensitive to some stimuli (ANG II, renal ischemia reperfusion injury), which may increase their vulnerability to renal injury (23).…”
Section: Age-related Decline In Renal Function In Iugr and Non-iugr Mmentioning
confidence: 98%
“…In the IUGR LPD females, it is possible that the initial congenital deficit combined with aging has markedly depleted renal functional reserve and, thus, counteracted the beneficial hormonal effects of circulating estrogen. In support of this idea, a congenital deficit in nephron number has been linked to an age-related decline in renal function in females in other animal programming models [including placental insufficiency (24,38), fetal uninephrectomy (54), and maternal nicotine (55)]. It has been suggested that kidneys with fewer nephrons are more sensitive to some stimuli (ANG II, renal ischemia reperfusion injury), which may increase their vulnerability to renal injury (23).…”
Section: Age-related Decline In Renal Function In Iugr and Non-iugr Mmentioning
confidence: 98%
“…In other studies in females, Intapad and colleagues found similar reductions in renal norepinephrine content after bilateral renal denervation in controls (213.9 ± 18.9 pg/mg vs. 30.2 ± 7.5 pg/mg protein) and in adult intrauterine growth‐restricted females (182 ± 5.9 vs. 29.9 ± 7.3 pg/mg protein) (Intapad et al. 2013). Although these colleagues are in our university, their renal norepinephrine levels were measured at Vanderbilt and ours were measured at the Medical College of Wisconsin.…”
Section: Discussionmentioning
confidence: 99%
“…60 Sympathetic nerve activity contributes to blood pressure maintenance, to the elevation in blood pressure in situations of overactivation (or impaired counterregulatory mechanisms) in many forms of chronic hypertension, and after deleterious perinatal conditions (such as IUGR) in both humans and experimental models. [61][62][63] Sympathetic nerve activity can also be activated by chronic inflammation (including through inflammatory cytokines secreted by adipose tissue) and increased expression of the RAS. 64 In infants born preterm, the sympathetic system is overactivated, and parasympathetic nervous system tone is deficient.…”
Section: Sympathetic Nerve Activitymentioning
confidence: 99%